Aromatic amino acid metabolism shapes autophagy-mediated adaptation to iron deprivation in glioblastoma cells - Kai Zhao; Lena Ludwig-Radtke; Yukai Wang; Tillmann Rusch; Christopher Nimsky; R. Verena Taudte; Jörg W. Bartsch (BioMetals, 2026)
Glioblastoma (GBM) displays profound iron dependence and metabolic plasticity, yet how iron deprivation interfaces with stress-response pathways and amino acid metabolism in GBM remains incompletely understood. Deferoxamine (DFO), an iron chelator and hypoxia mimetic, is widely used experimentally, but the integration of autophagy, apoptosis, and ferroptosis under DFO-induced stress is unclear. This study aims to clarify how iron chelation reshapes stress signaling and metabolism in GBM cells and to define the role of aromatic amino acid metabolism in autophagy-mediated adaptation to iron deprivation. U87 and U251 human GBM cell lines were treated with DFO in the presence or absence of pan-caspase inhibitor Q-VD-OPh, the autophagy inhibitor CQ, or L-phenylalanine and L-tyrosine. AlamarBlue assessed cell viability. Hypoxia, autophagy, apoptosis, and ferroptosis-related genes and proteins were analyzed by qPCR, western blotting, and immunofluorescence. Global metabolic alterations were profiled by untargeted UHPLC–HRMS-based metabolomics followed by multivariate and pathway enrichment analyses. DFO stabilized HIF-1α, robustly induced hypoxia-related gene expression, and reduced GBM cell viability, with U251 cells being more sensitive than U87. DFO induced an autophagy response associated with ULK1 upregulation and reduced mTOR transcript levels, accompanied by increased LC3-II and changes in p62 levels. A lysosomal inhibition-based assay further supported increased autophagic flux, and meanwhile engaged apoptosis, particularly in U251, where Q-VD-OPh significantly rescued viability. In contrast, DFO induces an iron-starvation signature and maintains ferroptosis-associated antioxidant markers (GPX4/SLC7A11). CQ co-treatment potentiated DFO cytotoxicity in both lines, indicating a cytoprotective role of autophagy. Metabolomics revealed extensive DFO-induced reprogramming of amino acid and central carbon metabolism, with aromatic amino acid metabolism emerging as key pathway. DFO decreased intracellular L-phenylalanine and L-tyrosine in U87 but not U251 cells. Combined L-P + L-T supplementation attenuated DFO-induced autophagic responses and further enhanced DFO-mediated cytotoxicity. Iron chelation by DFO establishes a multifaceted stress state in glioblastoma cells, characterized by hypoxia-like transcription, cytoprotective autophagy, apoptosis, and ferroptosis resistance, coupled to profound amino acid-centric metabolic remodeling. Aromatic amino acid metabolism modulates autophagic responses and a determinant of GBM susceptibility to iron deprivation. Therefore, targeting aromatic amino acid metabolism to disable protective autophagy may enhance the therapeutic efficacy of iron-based strategies in GBM.